(untitled) (Al-Academy, 2024)
Virtual graphics manifested in a modern and innovative design that captivates consumers with increased attractiveness and interactivity. Designers have become more focused on this field due to its utility in achieving remarkable results in marketing. Virtual graphics seamlessly blend reality and imagination to create stunning outcomes in the marketing process. This research explores the functional aspects of virtual graphics, specifically in the context of circular variations, changing sizes, and consistent, rhythmic movements within non-routine dynamics. The research is structured into four chapters: The first chapter addresses the research problem through the following question: "What are the functional aspects of virtual graphics in the design of advertising products?" The research aims to uncover the functional aspects of virtual graphics in graphic design. Key Findings: Virtual graphics, with their diverse artistic and technical methods, serve as a powerful attraction for viewers, conveying values in an enjoyable and innovative format. They navigate seamlessly between reality and imagination, bringing the imaginative elements into the realm of reality with a semblance of credibility. Virtual graphics delve into various intellectual and artistic depths, revealing captivating, engaging, easily understandable, impactful, and aesthetically rich images